Platelet Rich Plasma (PRP) Produces an Atherofibrotic Histophenotype During Craniofacial Bone Repair Due to Changes of Immunohistochemical Expression of Erk1/2, p38α/β, Adiponectin and Elevated Presence of Cells Exhibiting B-scavenger Receptor (CD36+) - Schroeder,Caroline Cristine (2016)
Abstract The platelet-extracellular matrix interaction in platelet rich plasma (PRP) through thrombospondin receptor-CD36 induces the secretion of growth factors responsible for cellular proliferation and differentiation during the repair process. Since CD36 also acts as a class B-scavenger-receptor for development of foam-like cells and mitogen-activated kinases, such as Erk1/2 and p38α/β, are important proteins activated by platelet growth factor, the aim of this study was to evaluate the immunohistochemical presence of CD36, Erk1/2, p38α/β during the bone repair treated and non-treated with PRP and to compare these results with the histomorphometry of repair. Simultaneously, the immunopresence of adiponectin was analyzed, which may contribute to osteogenesis at the same time it inhibits fibrosis and impairs adipogenesis and foam cell formation in the medullary area. An artificial bone defect measuring 5×1 mm was produced in the calvaria of 56 Wistar rats. The defects were randomly treated with autograft, autograft+PRP, PRP alone and sham. The animals were euthanized at 2 and 6 weeks post-surgery. Data were analyzed by ANOVA followed by non-parametric test Student Newman-Keuls (p<0.05) for histomorphometric and immunohistochemical interpretation. The results revealed that in specimens that received PRP the immunopositivity for Erk1/2, p38α/β and CD36 proteins increased significantly while the immunohistochemical expression of adiponectin decreased simultaneously. There was also an accentuated reduction of bone matrix deposition and increase of the medullary area represented by fibrosis and/or presence of foam-like cells, which exhibited immunophenotype CD36+adiponectin. The findings of this study suggest that PRP acted as an inhibitor of osteogenesis during the craniofacial bone repair and induced a pathological condition that mimics an atherofibrotic condition.